2012
DOI: 10.3389/fnhum.2012.00198
|View full text |Cite
|
Sign up to set email alerts
|

Recent and Past Musical Activity Predicts Cognitive Aging Variability: Direct Comparison with General Lifestyle Activities

Abstract: Studies evaluating the impact of modifiable lifestyle factors on cognition offer potential insights into sources of cognitive aging variability. Recently, we reported an association between extent of musical instrumental practice throughout the life span (greater than 10 years) on preserved cognitive functioning in advanced age. These findings raise the question of whether there are training-induced brain changes in musicians that can transfer to non-musical cognitive abilities to allow for compensation of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
104
5
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(130 citation statements)
references
References 74 publications
(114 reference statements)
18
104
5
3
Order By: Relevance
“…The observed association of early life instruction in a foreign language or music with higher level of cognition in old age is consistent with previous cross-sectional research showing that adults with expertise in a foreign language (Salvatierra & Rosselli, 2010; Gold et al, 2013) or music (Hanna-Pladdy & Mackay, 2011; Hanna-Pladdy & Gajewski, 2012)perform better on cognitive tests than adults without such expertise. We found no association between early life training and late-life rate of cognitive decline.…”
Section: Discussionsupporting
confidence: 90%
“…The observed association of early life instruction in a foreign language or music with higher level of cognition in old age is consistent with previous cross-sectional research showing that adults with expertise in a foreign language (Salvatierra & Rosselli, 2010; Gold et al, 2013) or music (Hanna-Pladdy & Mackay, 2011; Hanna-Pladdy & Gajewski, 2012)perform better on cognitive tests than adults without such expertise. We found no association between early life training and late-life rate of cognitive decline.…”
Section: Discussionsupporting
confidence: 90%
“…In line with previous studies investigating the role of art activities, including expressive writing, music, theatre or visual art, in cognition (see [21] for a comprehensive review), our findings suggest that weekly art practice is related to enhanced cognitive functioning. Prior studies report that weekly practice of music was related to higher working memory performance and visuo-motor speed [43,44], which is consistent with enhanced/protective effect of art activities on visuo-verbal memory, although artistic activities in our experiment did not include only music. Other research interested in theater, based on intervention paradigms, has shown that four weeks of practice of acting significantly improved cognitive functioning and decreased risk factors for dementia in mentally healthy older adults [45,46,47].…”
Section: Discussionsupporting
confidence: 86%
“…In addition to training studies, correlational studies suggest that musical training may have protective effects in aging. For instance, research examining lifestyle variables in older adults found an association between adult musicians who began musical training at an early age and those who maintained performance through adulthood (Hanna-Pladdy & Gajewski, 2012); the authors suggested that such enhancements in cognitive performance may compensate for age-related cognitive deficits. Collectively, these studies suggest that musical training has the capacity to increase general cognitive performance.…”
Section: Introductionmentioning
confidence: 99%